The Effect of Sales Accounting Information Systems on the Effectiveness of Sales Internal Control (Study on CV. Sumber Jaya) - Achmad Nur Fuad Chalimi (International Journal of Integrative Research, 2023)
Thisi studyi aims ito idetermine andi analyze ithe effect iof ithe iSales iAccounting iInformation System ion the iEffectiveness iof iInternal iSales Control. iThis istudy iused a purposive isampling technique with a total of 56 samples on CV. Source Jaya. Methods of data collection using questionnaires, documentation, and interviews. The idata ianalysis method iuses iSimple iLinear Regression iAnalysis iwith ithe help of the IBM SPSS iVersion i25 iSoftware iapplication. iThe results ishow ithat ithe iSales iAccounting Information iSystem ihas ia isignificant ipositive effect ion ithe iEffectiveness of Internal iSales Control, iithis iis iibecause iisales iiinformation can isupport ithe iicompany's iisuccess iin carrying iiout ithe iSales iAccounting Information System iprocess ithereby iimpacting ithe effectiveness iof iinternal isales icontrol. iThe conclusion iof ithis istudy iis ithat ithe ibetter ithe Sales iAccounting iInformation iSystem, ithe higher ithe iEffectiveness iof iInternal iSales Control iis icarried iout.